PENDAMPINGAN PELATIHAN SOFTWARE APLIKASI GUNA PERSIAPAN LKS DI SMK MUHAMMADIYAH SALAM - Emilya Ully Artha (STMIK Royal, 2020)
Abstract: Community service activities carried out at Muhammadiyah Salam Vocational School (SMK Muhammadiyah Salam), Salam Subdistrict, Magelang Regency so that the X grade (1st) students of Muhammadiyah Salam Vocational School can support computer creativity specifically for desktop applications for developing Software Engineering (RPL) skills. This service activity is carried out by using a method of mentoring for class X students through computer assistance / application programs such as database and desktop creation. The long-term goal is the preparation of class X students who have an interest in application software to participate in the Student Skills Competition (LKS) in the following period. This application software training at Muhammadiyah Vocational School does not have an RPL major, so students are selected to take part in this activity. The final output that will support this activity is student assistance in computer applications as a development aid for students in the field of programming / software engineering. In addition, the publication of the results of this service was in the community service journal Keywords: Community Service, Software Engineering, Application Software, Programming Abstrak: Kegiatan pengabdian masyarakat yang dilakukan di SMK Muhammadiyah Salam, Kecamatan Salam Kabupaten Magelang bertujuan agar para siswa kelas X SMK Muhammadiyah Salam dapat memiliki kreatifitas pada bidang komputer khususnya aplikasi desktop untuk pengembangan ketrampilan Rekayasa Perangkat Lunak (RPL). Kegiatan pengabdian ini dilaksanakan dengan menggunakan metode pendampingan secara komprehensif kepada pada siswa kelas X melalui pendampingan program/aplikasi komputer seperti pembuatan database dan desktop. Tujuan jangka panjangnya adalah mempersiapkan siswa kelas X yang mempunyai minat di bidang software aplikasi untuk mengikuti kegiatan Lomba Kompetensi Siswa (LKS) pada periode berikutnya. Pelatihan software aplikasi ini karena di SMK Muhammadiyah tidak memiliki jurusan RPL, sehingga mahasiswa diseleksi untuk mengikuti kegiatan ini. Luaran akhir yang akan dicapai dari kegiatan ini adalah meningkatnya kemampuan siswa dalam penggunaan aplikasi komputer sebagai alat pengembangan kreatifitas siswa dalam bidang pemrograman/rekayasa perangkat lunak. Selain itu adalah terpublikasinya hasil pengabdian ini dalam jurnal pengabdian masyarakat. Kata kunci: Pengabdian Masyarakat, Rekayasa Perangkat Lunak, Software Aplikasi, Pemrograman